Mediation Role of Organizational Commitments on The Influence of Rewards on Employee Turnover Intention - Abdul Gofur; Samsudin Samsudin; Munir Saputra (Majalah Ilmiah Bijak, 2021)
This research aims to analyze the mediating role of Organizational Commitment (M) on the effect of Reward (X) on Employee Turnover Intention (Y) using quantitative research. Data were obtained through interviews and questionnaires. The sample method of this research is non-probability sampling and a saturated sample technique of 43 employees as respondents. Data processing uses validity test, reliability test, t test, and path analysis assisted by SPSS Version 22.00 and Lisrel 8.8 programs to prove and answer four hypotheses. The results of research are: 1) The level of Organizational Commitment (M) is 0.80 (0.82 x 100 = 64%) is directly and positively influenced by the variation of Reward (X), 2) The level of Turnover Intention (Y) is 0.49 (0.492 x 100 = 24%) is directly influenced by variations of Reward (X), 3) The level of Turnover Intention (Y) is -0.19 (–0.192 x 100 = 3.61%) is negatively affected by variations of Organizational Commitment, 4) Reward (X) indirectly have no significant influenced on Turnover Intention (Y) of -0.15, T-count -0.97< 2.02 (t-table), although Reward (X) directly affect Turnover Intention (Y) but through indirect relationship Organizational Commitment (M) it turns out not significant.